A Condition Monitoring System for the Analysis of Bearing Distributed Faults - Irfan, M. (Institute of Electrical and Electronics Engineers Inc., 2019)
Condition monitoring is used in the plants to protect rotating equipments from failures and assist the management to plan a required shutdown before failure of the equipment. Bearings are the one of the important components in the rotating machines and premature failure of bearings causes huge financial loses. This paper attempts to analyze the bearing distributed faults through a non-invasive diagnostics approach. The distributed faults are created in the bearing using electric discharge machine. The test rig has been developed for the experimental investigations of the Park analysis approach. The results of the proposed Park approach have been analyzed and shown to be a reliable diagnostics approach for the bearing distributed faults. Â© 2019 IEEE.